2024
DOI: 10.1021/jacs.3c14744
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of the Structure and Magnetism to Spin Splitting in Hybrid Organic–Inorganic Perovskites

Ravi Kashikar,
Derick DeTellem,
Partha Sarathi Ghosh
et al.

Abstract: Hybrid organic−inorganic perovskites are famous for the diversity of their chemical compositions, phases, phase transitions, and associated physical properties. We use a combination of experimental and computational techniques to reveal a strong coupling between structure, magnetism, and spin splitting in a representative of the largest family of hybrid organic−inorganic perovskites: the formates. With the help of first-principles simulations, we find spin splitting in both conduction and valence bands of [NH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Multiferroic was initially coined by Aizu in 1968 with the theoretical identification of 42 species of simultaneously ferroelectric and ferroelastic phase transition . The famous inorganic Gd 2 (MoO 4 ) 3 with the fully ferroelectric–fully ferroelastic effect was predicted and successfully validated in 1968, serving as a typical model for fully multiferroic over subsequent decades. , The characteristic of a type of ferroelectric–ferroelastic crystal is that the concurrent alteration of the polarization vector alongside changes in the strain tensor, and vice versa, is fully ferroelectric and fully ferroelastic. Capitalizing on these dual ferroic effects, the development of high-precision electronic micropositioners, tunable radio frequency filters, compatible grating devices, and adaptive devices has become feasible. Furthermore, the synergy between ferroelectricity and ferroelasticity can markedly enhance material physical properties. , For example, You et al reported a hybrid perovskite multiferroic [Me 3 NCH 2 Cl]­CdCl 3 , whose illustrious electromechanical conversion performance has been proven to be closely related to the partial coupling of ferroelectricity and ferroelasticity. , Benefiting from the numerous advantages of intimate interplay between full ferroelectricity and full ferroelasticity, recently, a large amount of studies have focused on exploring multiferroic materials with ferroelectricity and ferroelasticity. However, constructing ferroelectric that is compatible with ferroelasticity has been a great challenge due to the strict requirements of crystallographic symmetry, reasonable symmetry breaking, and ingenious evolution of lattice parameters. …”
Section: Introductionmentioning
confidence: 99%
“…Multiferroic was initially coined by Aizu in 1968 with the theoretical identification of 42 species of simultaneously ferroelectric and ferroelastic phase transition . The famous inorganic Gd 2 (MoO 4 ) 3 with the fully ferroelectric–fully ferroelastic effect was predicted and successfully validated in 1968, serving as a typical model for fully multiferroic over subsequent decades. , The characteristic of a type of ferroelectric–ferroelastic crystal is that the concurrent alteration of the polarization vector alongside changes in the strain tensor, and vice versa, is fully ferroelectric and fully ferroelastic. Capitalizing on these dual ferroic effects, the development of high-precision electronic micropositioners, tunable radio frequency filters, compatible grating devices, and adaptive devices has become feasible. Furthermore, the synergy between ferroelectricity and ferroelasticity can markedly enhance material physical properties. , For example, You et al reported a hybrid perovskite multiferroic [Me 3 NCH 2 Cl]­CdCl 3 , whose illustrious electromechanical conversion performance has been proven to be closely related to the partial coupling of ferroelectricity and ferroelasticity. , Benefiting from the numerous advantages of intimate interplay between full ferroelectricity and full ferroelasticity, recently, a large amount of studies have focused on exploring multiferroic materials with ferroelectricity and ferroelasticity. However, constructing ferroelectric that is compatible with ferroelasticity has been a great challenge due to the strict requirements of crystallographic symmetry, reasonable symmetry breaking, and ingenious evolution of lattice parameters. …”
Section: Introductionmentioning
confidence: 99%